Refocusing regulatory exclusivities: Regulatory data protection and marketing exclusivity as forms of pharmaceutical innovation policy - Takalahti, Anni (fi=Turun yliopisto|en=University of Turku|, 2016)
Protection of innovation in the pharmaceutical industry has traditionally been realised through protection of inventions via patents. However, in the European Union regulatory exclusivities restricting market entry of generic products confer tailored, industry specific protection for final, marketable products. This paper retraces the protection conferred by the different forms of exclusivity and assesses them in the light of recent transparency policies of the European Medicines Agency. The purpose of the paper is to argue for rethinking the role of regulatory data as a key tool of innovation policy and for refocusing the attention from patents to the existing regulatory framework. After detailed assessment of the exclusivity regime, the paper identifies key areas of improvement calling for reassessment so as to promote better functioning of the regime as an incentive for accelerated innovation. While economic and public health analysis necessarily provide final answers as to necessity of reform, this paper provides a legal perspective to the issue, appraising the current regulatory framework and identifying areas for further analysis.